A paradigm analysis of valuation of intellectual property. (2016) - Uzma, Shigufta Hena
Over the past two decades intellectual property has become a concern and there are certain controversies about the recognition of intellectual property (IP), how will one value, protect and what are the potential benefits to the stakeholders. There have been several issues concerning IP for different stakeholders, the purpose for which IP is being used for; whether, for the licensing, transfer pricing, acquisition, accounting, taxation, fund raising, infringement issues, competitive analysis, external reporting, strategic management of IP, exploitation and management of IP. The aim of the present paper is to divulge various issues that come in the ambit of intellectual property, the recognition of intangible assets and how does it relate to the value maximisation of different stakeholders, what are the impediments to recognise IP, the valuation issues and methods, how reliable is valuation of IP and the relevance and reliability debate. The paper explores different methods and concepts used to measure the IP asset, and thereby, present conceptual frameworks for the valuation and management of IP.